Pendampingan Strategi Peningkatan Minat Beli Konsumen Melalui Marketing Mix Pada Home Industri Bolu Kijing - Zed, Etty Zuliawati; Kartini, Tri Mulyani; Kosim, Muhammad (Universitas Gajah Putih, Indonesia, 2023)
Business is very important, the Indonesian economy runs on business. Starting from large scale, medium to micro. Micro, Small and Medium Enterprises (MSMEs) themselves have made a significant contribution to economic growth but the impact of the Covid-19 Pandemic has reduced competitiveness, especially in the field of marketing(Purbantina et al., 2022). Likewise, the problem experienced by some Home Industries is the declining interest in buying from consumers, many factors have resulted in this including the many competitors from other parties, the lack of creation and innovation of our products, the lack of promotion and production management, and many more. In the world of marketing there is something called a marketing mix in which all marketing strategies around the 7P are explained. Therefore, this community service activity aims to help home industry business actors carry out marketing strategies to increase consumer buying interest through the marketing mix. This service activity provides assistance in understanding business actors, especially the Bolu Kijing home industry in increasing marketing capabilities so that they can increase buying interest by implementing a marketing mix by maximizing the use of existing technology in the digitalization era, especially the lifestyle of today's people who really like convenience.